PENGARUH MOTIVASI DAN DISIPLIN KERJATERHADAP KINERJA KARYAWAN PRODUKSI PADA PT. SIERAD PRODUCE, TBK BOGOR - Putri Nilam Kencana; Baliyah Munadjat; Windy Gustia Wardani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to determine whether there is an Influence of Motivation and Work Discipline on the Performance of Production Employees at PT. Sierad Produce, Tbk Bogor. The research method carried out in this writing is quantitative, while to obtain data is carried out by distributing questionnaires with respondents to 84 respondents using the slovin test. The analysis methods used are validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, product moment correlation, partial tests, simultaneous tests and coefficients of determination. The results showed that the influence of motivation and work discipline on the performance of production employees at PT. Sierad Produce, Tbk Bogor is currently good. The results of multiple regression analysis obtained Y = 14.770 + 0.315 X1 + 0.290 X2, then the value of constant (a) of 14.770 states that even without the influence of motivation and work discipline variables, employees still have an employee performance level of 14.770. The regression coefficient of 0.315 in the motivation variable, is a positive linear regression direction coefficient, meaning that for every increase in motivation by one unit, employee performance will increase by 0.315 assuming work discipline is considered constant. The regression coefficient of 0.290 in the labor discipline variable, is a positive linear regression direction coefficient, meaning that for every increase in work discipline by one unit, employee performance will increase by 0.290 assuming motivation is considered constant. With a coefficient of determination of 0.444, which means that the variance that occurs in employee performance variables is 44.4% determined by variables of motivation and work discipline, while the remaining 55.6% is determined by variables that are not careful.